Analisis Strategi Komunikasi Pemasaran Alcofee Co-Working Space - Fitri Fitri; Ria Bintan Napitupulu; Muhammad Rizky; Vina Liesty Indriani; Golan Hasan (Jurnal Mirai Management, 2022)
The purpose of the analysis carried out is to find out Integrated Marketing Communication has an influence on the marketing stage. Based on the results of data analysis, it can be concluded that Integrated Marketing Communication has a positive effect on the stages of purchasing decisions. Indicators of Integrated Marketing Communication (X) at AlCoffee carried out in this study are clear message content, attractive appearance, attractive incentives, easy to follow, various prizes, news credibility, company image, shopping atmosphere, attracting attention, targeted information, ease of information, ease of interaction, word of mouth, delivery method, and clarity of information. The indicator of company image has the most dominant influence, while the type of incentive that attracts the indicator has the lowest coefficient. Keywords: Coffee shop, SME, Communication Strategy, ERP